Knowledge, Attitude and Practice of blood donation among undergraduate medical students in Shimoga Institute of Medical Sciences - Nandan, Shilpa; S, Veena; Devadas, Vaishnavi M (International Journal of Health and Clinical Research, 2021)
Introduction:Blood donation is an important and integral part of our health care system and it needs no introduction to say that blood donation can save millions of lives across the world. India needs several million units of blood annually and we only see increase in the demand year after year. Voluntary blood donors are the low risk group of people who reduce the transmission of blood borne infections that mainly include HIV, HCV, HBsAg, Malaria, etc,. Young health care professionals that include medical students and doctors, who by the virtue of their training and medical practices, are expected to have sufficient knowledge about voluntary blood donation and it's benefits. Many myths and misconceptions hinder them to come forward and actively participate in voluntary blood donation. The low level of awareness and unsatisfactory voluntary blood donation practices among the medical students marks the need to conduct more such studies thereby helping the medical students to contribute actively towards voluntary blood donation.Methods:A cross-sectional study was conducted by giving the students a questionnaire that included the questions regarding knowledge attitude and practice of blood donation 85 students participated in the study. Consent was taken prior to the study. The questions were answered by the students and responses were collected immediately. Data was entered in the MS Excel sheet and was analyzed.Results :98.8% of the students had adequate knowledge of blood donation and 43% of the students had misconceptions. Students showed a positive attitude towards blood donation and 80% of the students opted for voluntary blood donation. Many students had not actively participated in blood donation, hence the practice of blood donation was poor.Conclusion :Young medical students, though enthusiastic and eligible to donate blood, due to lack of knowledge and misconceptions do not come forward and practice blood donation. They should be motivated and educated regarding blood donation. Need for blood donation and the scarcity of blood & blood products must be explained to the students. Blood donation camps on national festivals, college fests must be arranged periodically so that students come forward and participate actively in blood donation. Medical students in the healthcare institutions play a pivotal role in bridging the gap between the demand and the scarcity of blood and blood products.